2015
DOI: 10.1001/jamasurg.2014.2246
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Surgical and Anesthesia Staff at 10 Government Hospitals in Sierra Leone

Abstract: To address unmet surgical need in the long term, accredited local surgical specialization programs are required; training of nonphysician surgical practitioners may offer a short-term solution. To develop safe anesthesia care, governments and donors should focus on providing health care professionals with essential equipment and resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
(15 reference statements)
1
18
0
Order By: Relevance
“…The STP was planned in 2009 as Sierra Leone was recovering from a devastating civil war. This country, with 5·5 million inhabitants, at that time had only 167 MDs in clinical practice, poor output from the medical school and no formal postgraduate training available in surgery or obstetrics. Surgical care was not prioritized in the national health agenda, despite an extensive surgical disease burden and mortality, and there was more than 90 per cent unmet surgical need.…”
Section: Methodsmentioning
confidence: 99%
“…The STP was planned in 2009 as Sierra Leone was recovering from a devastating civil war. This country, with 5·5 million inhabitants, at that time had only 167 MDs in clinical practice, poor output from the medical school and no formal postgraduate training available in surgery or obstetrics. Surgical care was not prioritized in the national health agenda, despite an extensive surgical disease burden and mortality, and there was more than 90 per cent unmet surgical need.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is widely known that patients maintain respiratory drive and airway protective reflexes with ketamine anaesthesia, further research is also needed to address anaesthesia safety. The capacity to provide safe anaesthesia has been reported as very low, even as nurse anaesthetists are being trained to increase access to anaesthesia across the country 48. Most facilities in Sierra Leone lack the human resources and infrastructure to provide care for patients who are critically ill, which may contribute further to the high perioperative mortality 49…”
Section: Discussionmentioning
confidence: 99%
“…In Sierra Leone, caesarean sections are carried out by both physicians and associate clinicians,50 and most of the anaesthesia is provided by nurse anaesthetists 48. Such task sharing has a long history on the African continent,51–53 particularly for caesarean delivery, and in many cases with good results 53.…”
Section: Discussionmentioning
confidence: 99%
“…Before the EVD outbreak, there were ten consultant surgeons in the public government hospitals and an estimated twenty-six in private non-profit hospitals in Sierra Leone (41,42). The LCoGS demonstrated that a surgical workforce density of less than 20 per 100,000 specialist surgeons, anaesthesiologists, and obstetricians correlates with lower rates of maternal survival (5).…”
Section: Surgical Volumementioning
confidence: 99%